Seroprevalence of diphtheria and tetanus antibodies among children and adolescents in high- and low-immunization coverage areas in the Lao People’s Democratic Republic - Yuta Yokobori; Masaaki Iwaki; Miyuki Kimura; Noriko Kitamura; Haru Angelique Hoshino; Bandith Soumphonphakdy; Chansay Patthammavong; Bangone Tannavong; Amphai Khamsing; Phonethipsavanh Nouanthong; Mathida Thongseng; Masahiro Sano; et al. (PLoS ONE, 2025)
Introduction Diphtheria and tetanus remain significant public health concerns in low- and middle-income countries (LMICs), including the Lao People’s Democratic Republic (Lao PDR). Although national infant immunization coverage has improved, substantial subnational disparities persist, and no booster doses are administered beyond infancy. This study aimed to assess population-level immunity to diphtheria and tetanus among children and adolescents in high- and low-coverage areas of Lao PDR. Methods A cross-sectional sero-epidemiological survey was conducted from September to October 2024 in Oudomxay (high coverage) and Xaisomboun (low coverage) provinces. A total of 960 participants aged 1–19 years were selected through multistage cluster sampling. Demographic and vaccination data were collected, and dried blood spots were tested for anti-diphtheria and anti-tetanus immunoglobulin G (IgG) using enzyme-linked immunosorbent assay. Seropositivity was defined as IgG level ≥0.1 IU/mL for diphtheria and ≥0.16 IU/mL for tetanus. Multilevel multivariate logistic regression identified factors associated with seropositivity. Results A total of 960 participants were enrolled; the response rate was 100%. Overall, 79.1% of participants reported receiving the three-dose pentavalent vaccine (Penta3), with coverage higher in Oudomxay (91.9%) than in Xaisomboun (66.3%). Seropositivity rate for both diphtheria and tetanus displayed a U-shaped age distribution, declining among school-aged children. Oudomxay showed higher seropositivity for both diseases. Multivariate analysis revealed lower seropositivity among participants aged 5–14 years and Hmong participants. Penta3 was significantly associated with tetanus, but not diphtheria, seropositivity. Conclusions This study identified notable immunity gaps among school-aged children and ethnic minorities in Lao PDR. Findings support introducing WHO-recommended booster doses and implementing targeted strategies to enhance coverage equity and population-level protection.